A study on student retention among final year student of Bachelor in Administrative Science at UiTM Melaka City Campus / Muhammad Irsyaduddin Abdul Hameed and Syamsul Johari Jalaludin - Abdul Hameed, Muhammad Irsyaduddin; Jalaludin, Syamsul Johari (Faculty of Administrative Science and Policy Studies, 2013)
The study seeks to determine the factors of student’s retention among final year students of Bachelor Administrative Science at UiTM Melaka City Campus. A sample of 160 respondents had been selected for this study. The findings showed that the independent variables or factors that support our hypothesis are family support, institutional support, and technical support. It means that not all of these three factors determine their relationship with the factors of student retention. Purposive sampling will be used to distribute the questionnaire to selected respondents. Based on this finding, institutional support is the most contributors to the factor of student retention. While, two out of three independent variables have a significant relationship with the factors of student retention. This is due to the result of correlation coefficient that has been used. In conclusion, family support and technical support contribute to the factor of students retention among final year students.